Separation of azeotropic mixtures using protic ionic liquids as extraction solvents - Sosa, Julio E. (2020)
IF/00190/2014; IF/00210/2014; PTDC/EQU-EQU/29737/2017; PTDC/QEQ-FTT/3289/2014; IF/00210/2014/CP1244/CT0003; UID/QUI/50006/2019; POCI-01-0145-FEDER-007265; University of Pamplona, Internal Project 2-2017.